Comment on “The Geometric Structure of the Brain Fiber Pathways” - Catani, Marco; Bodi, Istvan; Dell’Acqua, Flavio (Science (American Association for the Advancement of Science), 2012)
Wedeen et al . (Reports, 30 March 2012, p. 1628) proposed a geometrical grid pattern in the brain that could help the understanding of the brain’s organization and connectivity. We show that whole-brain fiber crossing quantification does not support their theory. Our results suggest that the grid pattern is most likely an artifact attributable to the limitations of their method.